THE EMERGENCE OF GAUDIYA VAISHNAVISM IN MANIPUR AND ITS IMPACT ON NAT SANKIRTANA - Manna, Subhendu (International Journal of Research -GRANTHAALAYAH, 2020)
The Gaudiya Vaishnavism that emerged with Shri Chaitanya in the fifteenth century continued even after his passing in the hands of his disciples and spread to far-away Manipur. Bhagyachandra – the King of Manipur along with his daughter Bimbabati Devi, visited Nabadwip and established a temple to Lord Govinda which stands till today in the village called Manipuri in Nabadwip. Therefore, the strand of Bengal’s Gaudiya Vaishnavism that Bhagyachandra brought to Manipur continues to flow through the cultural life of the Manipuri people even today, a prime example of which is Nat Sankirtana. The influence of Gaudiya Vaishnavism on Nat Sankirtana is unparalleled.